Evaluation of mitochondrial D-Loop and 16SrRNA diversity among cultured Penaeus Monodon samples (Funded Work) - DEBABRATA MONDAL; NRIPENDRANATH MANDAL (International Journal of Pharma and Bio Sciences, 2019)
The giant black tiger shrimp, Penaeus monodon (Fabricius, 1798) is one of the most widely captured and cultured marine shrimp species and has a huge global economic impact. The last three decades, shrimp aquaculture has been threatened by various major virus outbreaks, mainly white spot syndrome virus. Therefore, evaluation of genetic diversity, as well as population genetic differentiation is required to identify overexploited regions of high-quality pond-reared P. monodon. In this study, the population genetic diversity of P. monodon was determined by the molecular data of the mitochondrial control region (mt D-Loop) and the 16SrRNA gene. The mitochondrial DNA (mtDNA) regions were highly AT-rich and a very high level of genetic diversity was observed. The diversity of 16SrRNA haplotypes was (0.963 ± 0.023), and the diversity of D-Loop haplotypes was (0.972 ± 0.017). The mitochondrial control region (D-Loop) was highly polymorphic and should be the potential markers for intraspecific population diversity study of P. monodon. The 16SrRNA would be the best marker for phylogenetic studies in P. monodon. Linkage disequilibrium analysis revealed that the increment of rare mutations and haplotypes. This study has a great significance to maintain high-quality pond-reared stock diversity, and also in accomplishing selective breeding.